Radiologic evaluation of a giant aneurysmal left circumflex coronary artery presenting with palpitation: A Cas of successful diagnosis - Mohammad Nasser Khattab, MD; Karam Alkounsol, MD; Anas Alrefai, MD; Alaa Haj Ali, MD; Fawzi Nabhani, MD; Ahmad Alayed, MD, FESC (Radiology Case Reports)
Coronary artery aneurysms (CAAs) are rare cardiovascular abnormalities often associated with conditions like atherosclerosis, connective tissue disorders, or vasculitis. We report a case of a 39-year-old woman presenting with palpitations and dysphagia, ultimately diagnosed with a giant aneurysmal left circumflex coronary artery using a multimodal imaging approach. Initial echocardiography identified a cystic lesion within the left atrium, prompting further evaluation with cardiac magnetic resonance (CMR), computed tomography (CT), and coronary catheterization. These modalities confirmed a large LCX aneurysm measuring 6.3 × 7.9 cm with left main coronary artery dilation. While surgical intervention was recommended, the patient opted for medical management. This case underscores the critical role of advanced imaging in diagnosing and managing complex cardiac conditions.